2020
DOI: 10.1002/ajmg.a.61915
|View full text |Cite
|
Sign up to set email alerts
|

Parenting stress in families of children with Prader–Willi syndrome

Abstract: Prader–Willi syndrome (PWS) is a neurodevelopmental disorder characterized by multiple endocrine, metabolic, respiratory, cognitive, and behavioral/psychiatric symptoms that may lead to severe emotional strain in their caregivers. In this study, we evaluated parenting stress by the Parenting Stress Index‐short form (PSI/SF) and parent‐reported behavioral symptoms by the Child Behavior Checklist (CBCL/6–18) in families of children with PWS. Sixty‐seven home‐resident PWS patients and their families were recruite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Strati et al showed the altered gut microbiota in Rett syndrome individuals is likely secondary to impairment in MECP2 functioning (Strati et al, 2016 ). Wong et al studied the parental distress in children with Prader Willi syndrome (another neurodevelopmental disorder) and they found that somatic symptoms were the only factor related to high parenting stress (Wong et al, 2021 ). More than one‐third of subjects in our cohort required second‐tier medications to manage constipation (i.e., not responding to dietary modifications or first‐tier medications).…”
Section: Discussionmentioning
confidence: 99%
“…Strati et al showed the altered gut microbiota in Rett syndrome individuals is likely secondary to impairment in MECP2 functioning (Strati et al, 2016 ). Wong et al studied the parental distress in children with Prader Willi syndrome (another neurodevelopmental disorder) and they found that somatic symptoms were the only factor related to high parenting stress (Wong et al, 2021 ). More than one‐third of subjects in our cohort required second‐tier medications to manage constipation (i.e., not responding to dietary modifications or first‐tier medications).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used the behavior task (CPT-3) to demonstrate attention problems in patients with PWS. Although ADHD is a common comorbidity in patients with PWS, the diagnosis discussed in previous studies has mostly relied on parent-reported questionnaires ( Wigren and Hansen, 2005 ; Wong et al, 2021a ). Our study escalates the behavioral evidence of ADHD in patients with PWS and opens the window to study genotype–phenotype correlations between ADHD and specific genetic dysfunction of PWS, which may improve treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Because attention is an important predictor of intelligence ( Schweizer and Moosbrugger, 2004 ), it is difficult to find a control group of patients with only an intellectual disability and no symptoms of ADHD. In addition, both intellectual disability and attention problems were stressors for families of PWS ( Wong et al, 2021a ); therefore, abnormal CPT-3 performance of patients with PWS indicated their significant functional deficits and highlighted the importance of dedicated medical and social support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parents unequivocally report fear for their child’s future, considering not only the management of further treatment, but also considering social acceptance. There is a relatively small number of researchers investigating the quality of families in which a child has PWS, and examining the impact of the disease on family functioning [ 36 ].…”
Section: Discussionmentioning
confidence: 99%